Utilization of nonpharmacological labor pain management and associated factors among healthcare providers in Ethiopia: a systematic review and meta-analysis - Agerie Mengistie Zeleke; Yosef Aragaw Gonete; Worku Chekol Tassew; Yeshiwas Ayale Ferede (BMC Pregnancy and Childbirth)
Abstract Background Health outcomes are a global priority, and the use of nonpharmacological methods for labor pain relief is recommended to improve these outcomes. However, there is a lack of a review regarding on the utilization of nonpharmacological labor pain management. Objectives this study aimed to assess the pooled utilization of nonpharmacological labor pain management and the associated factors among healthcare providers in Ethiopia. Methods The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed for this review. A total of 2837 articles were retrieved from international databases, including Scopus, PubMed, Web of Science, Science Direct, and National Digital Library repositories. The search for articles was conducted from February 1, 2024, to February 30, 2024. To assess the methodological quality Newcastle Ottawa Scale was utilized. Data extraction was performed using Excel, and the analysis was conducted with Stata 11 software.The effect size measurement utilization of nonpharmacological labor pain management was estimated using the Random Effect Mode. The Cochran’s Q test and I2 statistic were used to assess the heterogeneity of studies. The symmetry of the funnel plot and Egger’s test were used to check for publication bias. Results Fourteen studies met the eligibility criteria with a total sample size of 4,821. The overall pooled utilization of nonpharmacological labor pain management among healthcare provider was 45.48% (95% CI: 35.74–55.22). Healthcare providers aged 20–29 years (AOR: 4.10; 95% CI: 1.79–9.39), those having with knowledge about nonpharmacological pain management (AOR: 3.11; 95% CI: 1.88–5.16), and those who allowed companions to support laboring mothers (AOR: 3.37; 95% CI: 1.56–7.24) were determinants of outcome variables. Conclusion Over half of Ethiopian healthcare providers did not use nonpharmacological pain management during childbirth. Key factors healthcare providers aged 20–29, those with adequate knowledge, and healthcare providers’ ability who allowed companions to enter labor ward to support laboring mothers. Providing updated in-service training programs for older healthcare providers are recommended to utilize nonpharmacological pain management techniques. Policymakers should also create clear understand about obstetric guidelines to promote pain management during childbirth.